2006
DOI: 10.1002/ijc.22359
|View full text |Cite
|
Sign up to set email alerts
|

Complete loss of PTEN expression as a possible early prognostic marker for prostate cancer metastasis

Abstract: The EGF/IGF growth factors are potent mitogens that regulate cell proliferation and cell survival and are involved in prostate cancer development. Using laser microdissection technology and real-time PCR, together with immunohistochemistry, we have explored the growth factor and integrin dependent PI3-kinase/ PTEN/Akt signalling pathway in prostate cell lines and tumour samples by analysing EGF-R, IGF1-R, ILK, b3 integrin, PTEN and p-Akt protein expression. We provide evidence that loss of PTEN expression rath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
90
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 46 publications
6
90
0
1
Order By: Relevance
“…In previous studies, PTEN was tested in PCa and hyperplastic prostate tissues, and it was observed to be mainly expressed in PCa tissues and in the cell nuclei of hyperplastic prostate tissues (28,29). The expression of PTEN in PCa was significantly higher than that in prostate hyperplasia, which indicated that increased PTEN expression levels may be associated with the incidence of PCa (30,31). In the present study, treatment with DPPT significantly promoted PTEN protein expression in DU-145 cells.…”
Section: Discussionsupporting
confidence: 56%
“…In previous studies, PTEN was tested in PCa and hyperplastic prostate tissues, and it was observed to be mainly expressed in PCa tissues and in the cell nuclei of hyperplastic prostate tissues (28,29). The expression of PTEN in PCa was significantly higher than that in prostate hyperplasia, which indicated that increased PTEN expression levels may be associated with the incidence of PCa (30,31). In the present study, treatment with DPPT significantly promoted PTEN protein expression in DU-145 cells.…”
Section: Discussionsupporting
confidence: 56%
“…Finally, although not replicated in the Swedish cohort, we found attenuation of the potent tumour-suppressor phosphatase and tensin homologue, PTEN, in TMPRSS2 -ERG fusion-positive tumours. Loss of PTEN expression has been strongly associated with prostate cancer progression (Koksal et al, 2004;Bertram et al, 2006;Yoshimoto et al, 2006a;Schmitz et al, 2007) and has recently been implicated as cooperating with TMPRSS2 -ERG fusion in high-grade prostatic intraepithelial neoplasia King et al, 2009). Loss of PTEN results in PI3K activation, which in turn can be targeted with emerging modalities inhibiting PI3K or PI3K and mTor such as SF1126 and BEZ235, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] PTEN deletions are found in approximately 40% of localized prostate cancers. 8,14,[31][32][33][34][35][36][37][38][39][40][41][42][43][44] In advanced disease, fluorescence in situ hybridization (FISH) has identified hemizygous (loss of one copy) and homozygous (loss of both copies) PTEN deletions, 31,39,43,45,46 with the incidence of PTEN deletion approaching 70-80% of castrate-resistant tumors. 33,40,42,43 It has been shown that hemizygous PTEN deletions are associated with earlier biochemical relapse.…”
mentioning
confidence: 99%